Exploring Digital Therapeutics: Game-Based and eHealth Interventions in Mental Health Care: Potential, Challenges, and Policy Implications - Vindigni, Giovanni (British Journal of Healthcare and Medical Research, 2023)
This all-encompassing manuscript delves into a thorough examination of the prevailing case of inquiry regarding the utilization of games and eHealth promotions for the betterment of mental health treatment. At the core of the investigation are crucial motifs, such as the theoretical fundamentals behind digital therapeutics, their machinery, long-standing repercussions, inclusion and equity, hodological contemplations, and policy ramifications. The paper follows an orderly analysis technique, linking with both qualitative and quantitative studies from diverse databases to scrutinize the effectiveness and safety of game-based and eHealth interventions in mental health care. The comprehensive inspection reveals potential behavioral, emotional, and cognitive transformations brought about by these interventions, as well as their effects on mental well-being. In addition, the paper explores the therapies’ long-term impact, their safety for those with severe mental illnesses, and their accessibility and appropriateness for a variety of demographics. What sets this appraisal apart is its focus on hodological aspects, exploring how these interventions might influence the interconnectivity of different brain regions. The manuscript’s verdicts expose the substantial potential of games and eHealth interventions in mental health care, all while warning to exercise caution due to gaps in wisdom surrounding their prolonged impacts and safety. Furthermore, it raises substantial questions regarding inclusion, equity, and accessibility in the application of these digital therapies. To conclude, the paper underlines the necessity for more scrupulous, tactful research to determine the effectiveness and safety of these interventions, implying the importance of considering ethical and implementation aspects for policymakers. Despite the potential of these digital therapies, the manuscript stresses the prerequisite for continued research to guarantee the mental health of patients is looked after and amplified. The principle of economic efficiency is laid out in § 12 V of the German Social Code (SGB, Sozialgesetzbuch), which states that the benefits provided “must be sufficient, appropriate, and cost-effective and must not exceed the necessary.”In this manuscript, we argue that game-based and eHealth interventions in mental health care are effective, safe, have a long-term impact, and are inclusive. These digital interventions have the potential to contribute to better mental health outcomes, possibly at a lower cost than traditional therapies, and to be accessible to a variety of demographics, increasing the efficiency of resource use in mental health care, which leads to the economic efficiency of these digital interventions. However, the text also highlights shortcomings in understanding their long-term effects and safety, raising important questions for health economics and policy like cost-effectiveness over the long term and the economic implications of implementing these digital therapies in a safe and equitable manner. As suggested by the text, additional research is required to address these issues and make sure that the application of these interventions conforms to the principle of economic efficiency as stated in § 12 SGB.